2015
DOI: 10.4028/www.scientific.net/amr.1094.445
|View full text |Cite
|
Sign up to set email alerts
|

High-Efficiency Cut Blasting with Shell Radial Shaped Charge in Laboratory-Scale Blasting

Abstract: Due to the inefficiency problem of the cut blasting in rock excavation and rock breaking, a shell radial shaped charge device was proposed based of the ideal of ‘cutting to slotting’ and it was validated through experiments. For this device, the shell materials are used to be shaped materials and multiple shaped ring is designed on the circular tube. It can not only reduce charge quantity but also raise the utilization ratio of explosive energy. After explosion, multiple radial shaped charge jets can be formed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Over the years, some innovative methods have been developed for cutting blasting. For example, Chen et al [10] found the shell radial shaped charge effective in cutting blasting, for it can elevate blasting efficiency, boost cyclic advancement, and lower the drifting costs. Combining middle-space charging and toespace charging, Zhang et al [11] noticed that the cutting effect of vertical large-diameter cutholes is enhanced by central large-diameter cuthole, stage-by-stage cutting blasting, and deck toe-space charging.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, some innovative methods have been developed for cutting blasting. For example, Chen et al [10] found the shell radial shaped charge effective in cutting blasting, for it can elevate blasting efficiency, boost cyclic advancement, and lower the drifting costs. Combining middle-space charging and toespace charging, Zhang et al [11] noticed that the cutting effect of vertical large-diameter cutholes is enhanced by central large-diameter cuthole, stage-by-stage cutting blasting, and deck toe-space charging.…”
Section: Introductionmentioning
confidence: 99%
“…These devices have been widely used in the field of civil blast engineering [10,11]. Chen et al [12] invented a new type of jet cracker to improve the blasting efficiency and the length of cyclical footage. However, when the shaped charge is applied to the hard rock blasting, two disadvantages are observed.…”
Section: Shock and Vibrationmentioning
confidence: 99%